Norse Revival Transformations of Germanic Neopaganism - von Schnurbein, Stefanie (Studies in Critical Research on Religion, 2016)
Norse Revival examines international Germanic Neopaganism (Asatru). It investigates its origins in German ultra-nationalist movements around 1900, its attempt to gain respectability since the 1970s and its intersections with historical and current debates on race, religion, gender, and aesthetics. Readership: Those interested in the study of religion, rightwing social movements, the reception of Nordic myth and relations between alternative religion, social movements, academic thought and aesthetic currents.